The Effect of Perceived Over-Qualification on Turnover Intention From a Cognition Perspective - Chen, Guofu; Tang, Yanzhao; Su, Yawen (Frontiers in Psychology, 2021)
The mechanism of the boundary conditions between over-qualification and employees’ turnover remains unclear. The problem of turnover caused by over-qualification has become a new problem in organizational management. Therefore, based on 396 survey data in China, this study uses multi-factor ANOVA, hierarchical regression analysis, and bootstrap method to analyze the relationship between perceived over-qualification and turnover intention. The results show that perceived over-qualification is positively correlated with turnover intention. Self-efficacy plays a mediating role in the relation between perceived over-qualification and turnover intention. Professional identity has a counter-regulatory effect on the relation between perceived over-qualification and turnover intention. This research expands the influence boundary of perceived over-qualification and provides theoretical support for human resource management.